HOMESCHOOLING SEBAGAI PENDIDIKAN ALTERNATIF DI ERA MODERN - Fakiha, Ila; Ahmadi, Alfian Khuswaidinsyah (Universitas Panca Marga, 2020)
In the modern era, competition among educational institutions is getting tougher because it is demanded to be able to appreciate and develop students' abilities in the cognitive, affective, and psychomotor domains. These demands are not easy to actualize due to various factors in the learning process. Thus, there are some students and parents who lack confidence in formal institutions which are in fact favorite and trusted educational institutions. The emergence of the phenomenon of homeschooling is a choice in producing better quality. Homeschooling is informal education which is a choice for parents who want to actualize developments in aspects of cognition, psychomotor and even more flexible social aspects and conducive learning so that parents can monitor it directly and parents can know the child's development continuously. The act of selecting homeschooling as an alternative educational institution in the modern era is based on the motives and meaning of homeschooling. This research method uses a qualitative approach to the type of case studies, using a phenomenological perspective. While collecting data obtained by observation and interview methods. After the data is obtained, the next step is to analyze the data. The results of this study are: The meaning of homeschooling for students: 1) learning more 2) learning environment is more conducive and effective. While the meaning of homeschooling for parents: the freedom to choose lessons and talents that children want to pursue. The motives for choosing homeschooling: 1) there is a mismatch with previous formal schools, 2) accustomed to homeschooling since childhood, 3) learning difficulties in large classes, 4) difficulty controlling child development, 5) avoiding bulliying, 6) the cost of education can adjust the ability parents, 7) have a lot of time with family, 8) theoretical learning as well as practice, 9) the potential that exists in children is explored. Keywords: Homeschooling, Alternative Education, Rationality Actions, Modern